Comparison of sagittal and vertical changes of the maxillary first molars induced by the palatally applied Pendulum distalizing appliance and palatally_buccally applied 2k-loop appliance - حسن, علي; فادي خليل , (Latakia University Journal -Medical Sciences Series, 2022)
Three-dimensional control of molar movement is important during distalization . therefore, most of the research was directed to developing appliances that achieve sagittally and vertically controlled changes of the molar during distalization. Aim: To evaluate the sagittal and vertical changes of the maxillary first molars caused by distalization using both appliances (2k-loop) and (Pendulum), and to compare the effectiveness of distalization using both previous appliances. Materials and Methods: The research sample included 16 bilateral class II malocclusion patients who did not have upper second molars in the occlusal level, and they randomly divided into two groups: Group (P) treated with Pendulum device and group (2k) treated with (2k-loop) device. Changes were assessed using lateral cephalometric radiographs of the head. Results: The (p) group showed a significant distal move of the upper first molars by (3.18±0.32) mm, associated with distal tipping of the first molars (8.32±1.73 )º and significant extrusion by(0.87±3.46) mm , and the group (2K) showed a significant distal move of the upper first molar (3±0.52) mm with distal tipping of (3.46±1.66)º, the distal tipping was statistically significantly lower in the group (2k) with intrusion of the molars. Conclusions: Both appliances have the ability to make significant distalization of the upper first molars and achieve a first-class molar relationship, and the (2k-loop) appliance is superior to the (Pendulum) appliance in its ability to produce distalization of the molars with less distal tipping and with intrusion during distalization.